Incidence and risk factors for injury in non-elite netball. - McManus, Alexandra (Sports Medicine Australia, 2006)
This paper identifies the risk and protective factors for injury in non-elite netball. Three hundred and sixty eight non-elite netballers completed a baseline questionnaire at the commencement of the 1997 preseason. Participants were telephoned each month during the 1997 and 1998 playing seasons to provide details of their exposure at training and games and any injury experiences in the previous four weeks. The incidence of injury in this study was 14 injuries per 1000 player hours. The risk factors for injury were identified as: not warming up before a game (IRR 1.11, 95% CI 1.00 - 1.23) and not being open to new ideas (IRR 1.04, 95% CI 1.00 - 1.07). Training for four or more hours per week (IRR 0.66, 95% CI 0.45 - 0.98) and not sustaining an injury in the previous 12 months (IRR 0.58, 95% CI 0.43 - 0.79) were found to be protective against injury. The risk and protective factors for injury identified in this study can be used as the basis for the development of evidence-based injury prevention strategies that seek to reduce the risk of injury in sport. Injury prevention strategies should focus on the development of effective training programs that include netball-specific skills, activities and movements. Further investigation into the mechanisms associated with the risk and protective factors identified would provide further understanding of why these factors increase or decrease the risk of injury.